1997
DOI: 10.1103/physrevlett.79.5278
|View full text |Cite
|
Sign up to set email alerts
|

Novel Diffusion Mechanism on the GaAs(001) Surface: The Role of Adatom-Dimer Interaction

Abstract: Employing first principles total energy calculations we have studied the behavior of Ga and Al adatoms on the GaAs(001)-b2 surface. Beside the adsorption site we identify two diffusion channels that are characterized by different adatom-surface dimer interaction. Both affect the adatom migration: in one channel the adatom jumps across the surface dimers and leaves the dimer bonds intact; in the other one the dimer bonds are broken. The two channels are taken into account to derive effective adatom diffusion ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
133
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 30 publications
14
133
1
Order By: Relevance
“…Questions addressed with pseudopotentials provided by this code, or its earlier version, range from phase transitions [10,11], defects in semiconductors [12][13][14], the structure of and diffusion on surfaces of semiconductors [15][16][17], simple metals [18], and transition metals [19][20][21], up to surface reactions [22,23], including molecules [24,25] of first-row species.…”
Section: Nature Of the Physical Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions addressed with pseudopotentials provided by this code, or its earlier version, range from phase transitions [10,11], defects in semiconductors [12][13][14], the structure of and diffusion on surfaces of semiconductors [15][16][17], simple metals [18], and transition metals [19][20][21], up to surface reactions [22,23], including molecules [24,25] of first-row species.…”
Section: Nature Of the Physical Problemmentioning
confidence: 99%
“…Part 1 (program psgen) serves to generate the pseudopotentials using the schemes by Hamann [33] or by Troullier and Martins [34]. This combination provides efficient pseudopotentials for "canonical" applications like group IV and III-V semiconductors [9,10,[15][16][17]22,23], as well as for systems where first-row, transition or noble metal elements are present [11,[19][20][21]24,25], or where "semicore" d-states must be treated as valence states, like in GaN [41] or InN [14]. In such cases the strongly localized 2p and 3, 4, 5d valence states are readily handled with the Troullier-Martins scheme.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of DFT calculations, the potential energy surface (PES) of an adatom is the adequate concept to address the issue of diffusion. DFT calculations of potential energy surfaces for various GaAs(001) surfaces are available from the literature, both for Ga diffusion [39][40][41] as well as for As diffusion [42]. Most importantly, it was found (see Ref.…”
Section: A Present Understandingmentioning
confidence: 99%
“…Most importantly, it was found (see Ref. [40]) that Ga has its strongest adsorption site inside As surface dimers, thereby breaking the dimer bond. The picture evolving from these computational results suggests that a possible role of the Ga atoms in growth could be the breaking-up of existing As surface dimers, and the formation of locally Ga-rich environments that act as selective sites for adsorption of As 2 molecules from the gas phase.…”
Section: A Present Understandingmentioning
confidence: 99%
“…There, DFT calculations have shown that Ga adatoms have the ability to break the As-As bond of As surface dimers. 18 Later it was demonstrated that this splitting of surface As dimers by Ga adatoms is one of the key processes in homoepitaxy. 19 Therefore we studied the analogous process of an In adatom on InAs͑137͒A splitting the As surface dimer.…”
Section: A In Adatom Diffusion On Inas(137)mentioning
confidence: 99%